Online Monitoring of Muscle Activity During Walking for Bio-feedback and for Observing the Effects of Transcutaneous Electrical Stimulation - Bunt, Nathan D.; Moreno, Juan C.; Muller, Philipp; Seel, Thomas; Schauer, Thomas (Converging Clinical and Engineering Research on Neurorehabilitation II, 2017)
This contribution describes a method for real-time analysis of muscle activity over the gait cycle while simultaneously applying Functional Electrical Stimulation (FES) to the assessed muscles. Inertial sensors at the foot are used for real-time gait phase detection in order to synchronize the stimulation with the gait. An EMG analysis has been performed to cancel out stimulation artifacts, to filter the data and to extract the voluntary EMG activity. This corrected EMG signal has been rectified and low-pass filtered to produce an envelope that was parameterized as a function of the Gait Cycle Percentage (GCP). The volitional EMG activity profile has been averaged over five strides and can be presented as a moving average over the exercise duration. Initial evaluation with healthy subjects showed that this procedure is feasible to detect the expected volitional muscle activity profiles also during active electrical stimulation.
CRIS-Team Scopus Importer:2021-03-31